The transplants = 移植人. - Tan, Jingliang. (2013)
Min and Kang-Woo are a young couple born Singaporean but raised in China. As they struggle to adapt to their country after returning to Singapore for the first time, they grow increasingly estranged from one another and from the land they call their birthplace. A growing sense of unease accumulates and begins to haunt Min, who comes to find her emotions externalized and projected upon her surroundings. Her home begins to transform before her eyes in accordance to her feelings, until she no longer sees ceiling nor floor, walls nor windows; only decay and anxiety.